An Enzymatic Route to Selenazolines. Issue 5 (18th February 2013) - Koehnke, Jesko; Morawitz, Falk; Bent, Andrew F.; Houssen, Wael E.; Shirran, Sally L.; Fuszard, Matthew A.; Smellie, Iain A.; Botting, Catherine H.; Smith, Margaret C. M.; Jaspars, Marcel; Naismith, James H.
<x xml:space="preserve">Abstract</x> Ringing the changes: Selenazolines have applications in medicinal chemistry, but their synthesis is challenging. We report a new convenient and less toxic route to these heterocycles that starts from commercially available selenocysteine. The new route depends on a heterocyclase enzyme that creates oxazolines and thiazolines from serines/threonines and cysteines.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>